2017
DOI: 10.1063/1.5000888
|View full text |Cite
|
Sign up to set email alerts
|

Ions shear flow and electron field-aligned current produce ion acoustic waves in the oxygen-hydrogen ionospheric plasma

Abstract: It is pointed out that the ion acoustic waves (IAWs) are excited either by field-aligned shear flows or electron parallel current in oxygen-hydrogen (O-H) plasma of upper ionosphere. The purely growing D'Angelo instability becomes ion acoustic wave instability in the presence of second kind of ions within the framework of multi-fluid plasma model. On the other hand, kinetic theory is used to show that the growth rate of current driven ion acoustic wave overcomes the ion Landau damping. Out of four real roots c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In order to find the solution of equation (28), we follow the method given by Demiray [40] and shift to a commoving frame…”
Section: Analytical Solution Of Dkp Equationmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to find the solution of equation (28), we follow the method given by Demiray [40] and shift to a commoving frame…”
Section: Analytical Solution Of Dkp Equationmentioning
confidence: 99%
“…The ionized oxygen ion number density is larger than the hydrogen number density. At the peak of the F-region which is situated at a height of 300 km, the number density of electrons and ions is at its maximum value [5]. Number density of hydrogen ions is dominant at an altitude of 1000 km.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrostatic DLs in unmagnetized and magnetized plasmas have been studied in electron ion plasma . It has been shown recently that in oxygen‐hydrogen plasma of upper ionosphere, the IAWs are excited by the ion field‐aligned shear flow at several different low frequencies and wavelengths. In the case of negative shear, these waves are modified and are excited by the electron parallel current in the F ‐region ionosphere where T i ≤ T e while T i ( T e ) is ion (electron) temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Ganguli et al 15 suggested that even a small amount of velocity shear in the flow is sufficient to excite a large-scale, Kelvin-Helmholtz mode, and can be a potential source for ion heating through wave generation. Recently, Saleem et al 16 theoretically proved that both ion shear flows and electron field-aligned current (FAC) can produce ion acoustic turbulence, assuming multi-species (O + -H + ) plasmas under realistic ionosphere conditions. Both of these shear-driven mechanisms can contribute to the anomalous resistivity as well.…”
mentioning
confidence: 99%